Abiraterone, Orteronel, Enzalutamide and Docetaxel: Sequential or Combined Therapy? - Chen, Ming-kun; Liang, Zhi-jian; Luo, Dao-Sheng; Xue, Kang-yi; Liao, De-ying; Li, Zheshen; Yu, Yuzhong; Chen, Zhe-Sheng; Zhao, Shan-Chao (Frontiers in Pharmacology, 2022)
Objective: To summarize the current therapeutic status using chemotherapeutic agent docetaxel and endocrine therapeutic agents (ARAT, abiraterone, orteronel or enzalutamide) for the treatment of metastatic castration-resistant prostate cancer (mCRPC), including sequential therapy and combined therapy, to promote the consensus on the optimal regimen for achieving superior treatment efficacy. Methods: Through literature search in PubMed, articles with the following relevant keywords were collected and anlyzed: CRPC, abiraterone, orteronel and enzalutamide, median survival, overall survival, prostate specific antigen (PSA), PSA response rate and median radiologic progression-free survival. Results: Fifty-eight articles were obtained and analyzed in this review. These articles included androgen axis-targeting agents after docetaxel, docetaxel after androgen axis-targeting agents, Triple sequential and combination therapy, covering four current drugs for mCRPC treatment: docetaxel, abiraterone, orteronel, and enzalutamide. It was found that there may be some cross-resistance between androgen axis-targeting agents, which will reduce the efficacy of subsequent drug treatment . Although neither of the studies of using combination therapy showed serious drug toxicity, the efficacy of sequential therapy was not as good as expected. Most adverse reactions after treatment were reported to be level 1-2. Conclusions: Based on the results of the current studies, abiraterone followed by enzalutamide treatment is the best sequential treatment for most docetaxel-naïve patients. This treatment achieves not only good OS, but also PFS and PSA response rates. In addition, for patients who have previously failed docetaxel treatment, enzalutamide is the best choice as the subsequent treatment.